Omental Pouch Technique for Combined Site Islet Autotransplantation Following Total Pancreatectomy - Stice, Mark J. (Cell Transplant, 2018)
Total pancreatectomy and islet autotransplantation (TPIAT) is an effective treatment for selected patients with chronic pancreatitis. The portal circulation is the standard infusion site for islet transplant, but marked elevation of portal pressures may prevent complete islet infusion. Herein we report a novel technique of combined site islet autotransplantation using an omental pouch. This technique may be useful when technical limitations prevent complete intraportal transplantation. In four TPIAT recipients with intraoperative issues precluding the complete intraportal infusion of islets, an omental pouch was created to contain the remaining islet mass. Patients were monitored for complications, and islet graft function was assessed using mixed meal tolerance testing and compared with matched controls who received only intraportally transplanted islets. All patients had decreasing insulin requirements as their recovery progressed. At 3 months follow-up there were no significant differences in glycemic control or graft function for the combined site recipients compared with their matched controls who only received an intraportal islet infusion. The omentum has potentially desirable qualities such as accessibility, capacity, and systemic/portal vascularity comparable to the native pancreas. The omental pouch technique may represent a safe and effective alternate site for islet autotransplantation. Further study is needed to confirm these findings.